Erythema Nodosum in Children: A Narrative Review and a Practical Approach - Sandra Trapani; Chiara Rubino; Lorenzo Lodi; Massimo Resti; Giuseppe Indolfi (MDPI AG, 2022)
Erythema nodosum (EN) is the most frequent form of panniculitis in children. We performed a literature review analyzing studies on pediatric EN published from 1990 to February 2022. EN is rare in pediatric age. It can be primary/idiopathic in 23-55% cases, or secondary in 47-77% cases. Secondary EN is related to a wide variety of conditions including infectious diseases, autoimmune disorders, malignancy, drugs, vaccinations, and pregnancy. The diagnosis of EN is clinical, based on the acute appearance of painful and red nodules localized to lower limbs, bilaterally distributed. If EN is diagnosed, basic work-up should include inflammatory markers, serum aminotransferases, lactate dehydrogenase, creatinine, protein electrophoresis, immunoglobulins, testing for streptococcal infection, and a tuberculin skin test. Based on the medical history and associated manifestations, further laboratory and radiological exams should be performed. The prognosis of EN is excellent, with spontaneous resolution in most patients within 2-6 weeks. Treatment, if needed, is addressed to the underlying condition. Despite being a rare manifestation in children, EN can be isolated or the first manifestation of a systemic or infectious condition. EN diagnosis is clinical, and a high index of suspicion is needed to perform investigations for the underlying disorders.